2020
DOI: 10.1210/clinem/dgaa650
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Chronic LH-Testosterone Axis Suppression in Male Macroprolactinomas With Normoprolactinemia on Cabergoline

Abstract: Context Data regarding prevalence, predictors, and mechanisms of persistent hypogonadotropic hypogonadism (HH) in males with a macroprolactinoma who achieve normoprolactinemia on dopamine-agonist therapy is limited. None of the previous studies provide cut-offs to predict the achievement of eugonadism. Objective To evaluate the prevalence of persistent HH and its determinants in males with a macroprolactinoma who achieve norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Some studies have reported different results. In 2020, Sehemby et al [ 66 ] studied a group of hypogonadal patients in which the PRL levels were restored to the normal range after treatment with cabergoline; the LH–testosterone axis remained suppressed in these men. This phenomenon was also described in a 2014 study by Shimon and Benbassat [ 67 ]; after 3 years of follow-up, only 26.7% of patients were found to have recovered.…”
Section: Changes In Male Gonadal Function After Treatment Of Pituitar...mentioning
confidence: 99%
“…Some studies have reported different results. In 2020, Sehemby et al [ 66 ] studied a group of hypogonadal patients in which the PRL levels were restored to the normal range after treatment with cabergoline; the LH–testosterone axis remained suppressed in these men. This phenomenon was also described in a 2014 study by Shimon and Benbassat [ 67 ]; after 3 years of follow-up, only 26.7% of patients were found to have recovered.…”
Section: Changes In Male Gonadal Function After Treatment Of Pituitar...mentioning
confidence: 99%
“…In their study, Sehemby et al [11] demonstrated selective suppression of the LH-testosterone axis (without suppression of the FSH-inhibin B axis) and thus they suggest that "chronic functional modi cation" of the hypothalamus, and not gonadotroph cell damage, is the biological mechanism of persistent HH.…”
Section: Discussionmentioning
confidence: 97%
“…In 2020, Sehemby et al [11] studied a cohort of 30 men, and found high rate of baseline central hypogonadism of 100%. All men included achieved normoprolactinemia with cabergoline therapy, and yet 73% of men had HH persistence at the end of the study period (median follow-up of 2 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are not enough data regarding predictors of long-lasting/persisting hypogonadism. In a recent retrospective study with a follow-up of only 2 years, hypogonadism persisted in 74% of patients after PRL normalization with Cab; the higher PRL levels and tumor size, the lower the chance of normalizing testosterone levels ( 154 ). In another study, long-term treatment (median: 3 years) was necessary to obtain normalization of hyperprolactinemia and reversal of hypogonadism ( 155 ).…”
Section: Therapeutic Issuesmentioning
confidence: 99%